The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.4049/jimmunol.166.3.1499
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Human Dendritic Cells by Dengue Virus Causes Cell Maturation and Cytokine Production

Abstract: Dengue virus (DV) infection is a major problem in public health. It can cause fatal diseases such as Dengue hemorrhagic fever and Dengue shock syndrome. Dendritic cells (DC) are professional APCs required for establishing a primary immune response. Here, we investigated the role of human PBMC-derived DC in DV infection. Using different techniques, including plaque assay, flow cytometry analysis, nested RT-PCR, and confocal microscope and electron microscope examinations, we show that DV can enter cultured huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
249
4
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(274 citation statements)
references
References 75 publications
16
249
4
4
Order By: Relevance
“…3A indicate that the anti-DV IFN-g response of gd T cells is also regulated by type I IFN. However, significant amounts of type I IFN are released by purified cultures of DVinfected DC (26,34,35), so that supplementing the culture medium with type I IFN, even at doses as high as 10,000 U/ml, did not increase the anti-DV IFN-g response of purified gd T cells (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A indicate that the anti-DV IFN-g response of gd T cells is also regulated by type I IFN. However, significant amounts of type I IFN are released by purified cultures of DVinfected DC (26,34,35), so that supplementing the culture medium with type I IFN, even at doses as high as 10,000 U/ml, did not increase the anti-DV IFN-g response of purified gd T cells (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Although DV-infected DC produce significant amounts of type I IFN (26,34,35), at levels that are not limiting for IFN-g production by gd T cells (Fig. 4C), the amount of IL-18 that is released by these infected cells is sufficient only for a basal anti-DV response.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that OBP-301-infected oncolytic tumor cells efficiently stimulated immature DCs to produce greater amounts of IFN-g and IL-12 than apoptotic and necrotic cells, and that such stimulation led to DC maturation. Viral infection itself has been reported to activate DCs to secrete pro-or anti-inflammatory cytokines, which can drive DCs to undergo the maturation process (Ho et al, 2001); the observation that OBP-301 alone had no effect on cytokine production by DCs, however, indicates that OBP-301 itself may be less infective or stimulatory to DCs. The result is consistent with our finding that OBP-301 attenuated replication as well as cytotoxicity in human normal cells.…”
Section: Virus-mediated Oncolysis Y Endo Et Almentioning
confidence: 99%
“…Human myeloid DC could be induced to mature and upregulate CD1d either directly through their own virusrecognizing pattern recognition receptors or indirectly through IFN-a released by stimulated human pDC. In addition, type I IFN is released by myeloid DC in response to viruses [62,63] and may act via a paracrine or autocrine loop [64]. As a consequence of CD1d-enhancing mechanisms, NKT cells are activated by recognition of either an endogenous, stress-induced or viral ligand.…”
Section: Discussionmentioning
confidence: 99%